Ethanol fermentation from Leucaena leucocephala seeds / Atik Zufar Mohd Razaki - Atik Zufar, Mohd Razaki (2018)
Nowadays, utilization of renewable fuel from biomass such as bioethanol is gaining a worldwide attention. Due to the global demand for bioethanol production, edible biomass such as corn and sugarcane could not be the feedstock to solve this issue as their primary use is for food production. Hence, Leucaena leucocephala (non-edible biomass) would be a possible alternative to replace edible biomass. This research deals with seeds of Leucaena leucocephala because there is a limited study on conversion of cellulose obtained from Leucaena leucocephala seeds into bioethanol and the seeds are normally left unused. In this study, therefore, evaluation of fermentation parameters such as days of fermentation, amount of sugar, amount of yeast and pH range was studied in order to find optimum parameters. Optimum days of fermentation, amount of sugar, amount of yeast and pH range were 3 days, 20 g, 3 g as well as between 4.0 – 4.9. Optimum parameters are important to produce high yield bioethanol from cellulose obtained from Leucaena leucocephala.